UPAYA GURU DALAM MENGEMBANGKAN EFEKTIVITAS KELOMPOK SEBAYA KELAS V MADRASAH IBTIDAIYAH (MI) MUHAMMADIYAH SUKAJATI HAURGEULIS - Rizky Amelia Ramadhanti; Abdur Rahim (JOEL: Journal of Educational and Language Research, 2023)
For learning that pays little attention to individual differences and peer groups towards children based on the wishes of the teacher, it will be difficult to deliver peer groups according to learning objectives. The purpose of this study is for teachers to be able to manage peer groups effectively, efficiently and on target in managing classes in the learning process at Muhammadiyah Sukajati Haurgeulis Islamic Elementary School (MI). This study used a type of qualitative research qualitative research collection technique, namely data collection through observation, interviews, questionnaires and documentation with a sample size of 20 students from 2 study groups for class V, namely from class 5A consisting of 23 students and class 5B. consisting of 23 people, totaling 46 students from the number of students who are in Muhammadiyah elementary school (MI) Sukajati Haurgeulis. The results of the study show that: there are those who like to study independently or study together with peers and there are also those who have difficulty learning independently or in groups by discussing with class 5 MI Muhammadiyah Sukajati Haurgeulis.